Decreased thickness of the lower trapezius muscle in patients with unilateral neck pain - Sureeporn Uthaikhup (2018)
© 2015 Wiley Periodicals, Inc. Introduction: Thickness of the lower trapezius muscle in patients with neck pain has not been established. We examined the thickness of the lower trapezius muscle in patients with and without unilateral neck pain. Methods: Twenty women with unilateral (right) neck pain and 20 matched controls participated in the study. Thickness of the lower trapezius muscles was measured bilaterally at rest (0 ° and 120 ° of shoulder abduction) and during contraction (120 ° of shoulder abduction) using ultrasound imaging. Results: The neck pain group had smaller thickness of the lower trapezius muscle on the painful side compared with controls both at rest and during contraction (P < 0.05). However, the percentage change in the lower trapezius thickness from rest to contraction (120 ° of shoulder abduction) was not different between groups (P > 0.05). Conclusions: Patients with neck pain had smaller thickness of the lower trapezius muscle on the painful side compared with healthy controls. Muscle Nerve 54: 439–443, 2016.